Speech development in inclusive classrooms - Gasimova Tanzila (Interdisciplinary Science Studies, 2025)
The philosophy of inclusive education ensures the right and opportunity for all children, including those with special educational needs, to study together with their peers in the same classroom environment. All children, regardless of race, religion, gender, health conditions, or social background, are included in this concept. The main goal of inclusive education is to maximize each learner’s potential, eliminate discrimination, and fully integrate them into society. The modern education system, based on an inclusive approach, aims to provide equal learning opportunities for children with different developmental levels, learning difficulties, speech disorders, and psychological characteristics. In this context, work on speech development not only improves language skills but also contributes to socialization, cooperation, emotional expression, and the formation of communicative culture. The development of speech skills in an inclusive classroom is considered one of the key indicators of the quality of instruction, as children acquire knowledge, express their ideas, and communicate effectively with peers through speech. Therefore, the systematic and purposeful organization of speech development work should be at the center of the educational process in inclusive settings.